On the Solution of the Linear Set-valued Homogeneous Cauchy Problem with the Hukuhara Derivative - Plotnikov, Andrej (Моделювання, керування та інформаційні технології, 2025)
The paper considers a linear set-valued homogeneous Cauchy problem with the Hukuhara derivative and provides its analytical solution. У статті розглядається лінійна однорідна задача Коші з багатозначними значеннями та похідною Хукухари та надається її аналітичний розв'язок.